ANTIOXIDANT ACTIVITY OF ETHYL ACETATE EXTRACT OF NUTMEG (Myristica fragrans Houtt) STEM BARK - Ilham Maulana; Binawati Ginting; Nurdin Nurdin; Saiful Fakri (Universitas Syiah Kuala, 2019)
Antioxidant activity test for the extract of ethyl acetate nutmeg stem bark (Myristica fragrans Houtt) was carried out using 2,2-diphenyl-1picrylhydrazil (DPPH). The test results of antioxidant activity of ethyl acetate nutmeg stem bark extract with DPPH method at a concentration of 25 ppm, 50 ppm and 100 ppm obtained IC50 value = 68.14 ppm with IC50 value of vitamin C (as positive control) 3.657 ppm. The results of column chromatographic separation of ethyl acetate nutmeg stem bark extract obtained 5 combined fractions namely MFEK 1, MFEK 2, MFEK 3, MFEK 4 and MFEK 5. The test results of the fraction antioxidant activity in a good category were the MFEK 1 fraction. The MFEK 2 fraction to MFEK 5 showed an antioxidant activity lower than compared to the ethyl acetate extract. This shows that the ethyl acetate nutmeg stem bark extract has a better inhibitory activity, because there are several active compounds contained in the extract which can inhibit free radicals, so the IC50 value of the extract is better than the fractions.